Large amplitude motions in cyclopentene and 1-butene: quantum chemical insights into the ground- and excited state potential energy surfaces - Knippenberg, Stefan; Dreuw, Andreas (Zeitschrift für physikalische Chemie, 2011)
The ring-puckering motion in cyclopentene as well as the hindered internal rotation around the central C-C bond in 1-butene have been studied by high-level quantum chemical calculations. Relevant potential energy surfaces of these molecules along these large-amplitude motions are provided as well as rotational constants are given allowing for thorough comparison with recent results from time-resolved femtosecond degenerate four-wave mixing (fs DFWM) spectroscopy. Emphasis is put on the performance of various post-Hartree Fock methods, the required level of electron correlation as well as the basis set quality.
Gesehen am 18.12.2017